2018
DOI: 10.15548/jebi.v3i2.177
|View full text |Cite
|
Sign up to set email alerts
|

Maksimalisasi Potensi Zakat Melalui Peningkatan Kesadaran Masyarakat

Abstract: The theme of the article is: zakat management. The purpose of the article is: to examine the potential of zakat to overcome poverty. The research method used in this research is qualitative research methods. Zakat is a property that must be issued by a Muslim to give to those who have the right to receive it in accordance with Islamic law. The analysis shows that zakat can reduce the number of poor families from 84% to 74%. This shows the extraordinary potential of zakat which can prosper the people. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 0 publications
1
9
0
16
Order By: Relevance
“…Hal ini yang menjadikan masalah dalam pengumpulan atau kesadaran masyarakat Indonesia pada masa sekarang. Kesenjangan antara dana yang terkumpul dengan dana yang disalurkan tersebut menandakan bahwa adanya masalah dalam marketing dan peruntukannya terkait dengan kepercayaan masyarakat terhadap Lembaga pengelola zakat selama ini (Nurhasanah & Suryani, 2018). Hal ini juga didukung oleh Lubis (2014) yang menyatakan bahwa salah satu faktor keengganan masyarakat membayar zakat pada Badan Amil Zakat adalah kurangnya kepercayaan masyarakat terhadap BAZIS/LAZ.…”
Section: Pendahuluanunclassified
“…Hal ini yang menjadikan masalah dalam pengumpulan atau kesadaran masyarakat Indonesia pada masa sekarang. Kesenjangan antara dana yang terkumpul dengan dana yang disalurkan tersebut menandakan bahwa adanya masalah dalam marketing dan peruntukannya terkait dengan kepercayaan masyarakat terhadap Lembaga pengelola zakat selama ini (Nurhasanah & Suryani, 2018). Hal ini juga didukung oleh Lubis (2014) yang menyatakan bahwa salah satu faktor keengganan masyarakat membayar zakat pada Badan Amil Zakat adalah kurangnya kepercayaan masyarakat terhadap BAZIS/LAZ.…”
Section: Pendahuluanunclassified
“…The potential for receiving zakat can be increased by empowering zakat especially productive zakat (Amelia, 2016). Nurhasanah found that to explore the potential of zakat is done by increasing public awareness of the importance of the distribution of zakat and the benefits of zakat on efforts to reduce poverty and social inequality (Nurhasanah & Suryani, 2018). Muneeza dan Hassan (2014) explained that Amil zakat companies and institutions need a good Islamic governance code 'and apply Islamic legal principles to optimize the potential and management of zakat.…”
Section: Potential Acceptance Of Zakat As An Instrument Of Wealth Dismentioning
confidence: 99%
“…Zakat memiliki potensi (Nurhasanah, 2018) yang luar biasa untuk mengatasi kemiskinan bangsa dan mensejahterakan umat. Potensi ini harus disadari oleh seluruh umat muslim agar dana yang dikumpulkan melalui zakat bias mensejahterahkan umat.…”
Section: Indonesiaunclassified